WINDS OF CHANGE AND LINKS OF CONTINUITY: A STUDY ON THE MERCHANT GROUPS OF KERALA AND THE CHANNELS OF THEIR TRADE, 1000-1800 - PIUS MALEKANDATHIL (JESHO 50,2-3_f8_259-286II 7/26/07, 2007)
The diverse merchant groups that participated in maritime trade emanating from the various exchange centers of Kerala during this period acted within the framework of certain socioeconomic conditions that ensured a remarkable degree of continuity as far as their organizational arrangements and distribution networks were concerned.Familiarization with frequent socio-political changes in the maritime exchange centers of Kerala, which were then exposed to frequent expansionist moves of inland rulers in the initial phase and of European commercial powers in the later periods, gave a great amount of adaptability to the different mercantile groups involved in its maritime trade, capacitating them to develop multiple survival strategies. Different segments of traders, who were unified by the commonality of religion, as in the case of Muslim merchants, developed diverse but better strategies to overcome Portuguese control systems as well as to ensure continuity in trade.